Γδ T Cell and Other Immune Cells Crosstalk in Cellular Immunity. (6th March 2014) - He, Ying; Wu, Kangni; Hu, Yongxian; Sheng, Lixia; Tie, Ruxiu; Wang, Binsheng; Huang, He
Abstract : γ δ T cells have been recognized as effectors with immunomodulatory functions in cellular immunity. These abilities enable them to interact with other immune cells, thus having the potential for treatment of various immune-mediated diseases with adoptive cell therapy. So far, the interactions between γ δ T cell and other immune cells have not been well defined. Here we will discuss the interactivities among them and the perspective on γ δ T cells for their use in immunotherapy could be imagined. The understanding of the crosstalk among the immune cells in immunopathology might be beneficial for the clinical application of γ δ T cell.